2016
DOI: 10.2147/lra.s64279
|View full text |Cite
|
Sign up to set email alerts
|

Managing anesthesia  for cesarean section in obese patients: current perspectives

Abstract: Obesity is a worldwide epidemic. It is associated with increased comorbidities and increased maternal, fetal, and neonatal complications. The risk of cesarean delivery is also increased in obese parturients. Anesthetic management of the obese parturient is challenging and requires adequate planning. Therefore, those patients should be referred to antenatal anesthetic consultation. Anesthesia-related complications and maternal mortality are increased in this patient population. The risk of difficult intubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 115 publications
0
42
0
Order By: Relevance
“…Obese women have reduced lumbar cerebrospinal fluid (CSF) volume which can be inversely related to cephalad spread of local anesthetics. 14 Carvalho et al 7 and Lee et al 15 found no association with BMI and the height of spinal anesthesia for obese women undergoing a CD. However, the study sizes are small and use methods that assume large sample properties.…”
mentioning
confidence: 94%
“…Obese women have reduced lumbar cerebrospinal fluid (CSF) volume which can be inversely related to cephalad spread of local anesthetics. 14 Carvalho et al 7 and Lee et al 15 found no association with BMI and the height of spinal anesthesia for obese women undergoing a CD. However, the study sizes are small and use methods that assume large sample properties.…”
mentioning
confidence: 94%
“…However, by adding opioids such as sufentanil to bupivacaine, the required dose of local anesthetic is decreased. This may result in lower side effects and improved quality of spinal anesthesia and postoperative analgesia ( 7 , 8 ). Earlier studies have examined the effects of adding various amounts of sufentanil to a fixed dose of local anesthetic to find the optimum dose of adjuvant ( 9 - 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, complications from anaesthesia are higher in obese patients compared to normal weight patients [ 36 ]. There is increased risk of incorrectly placing an epidural in obese patients as the distance to the epidural space is greater with increased BMI [ 36 , 37 ], risk of difficult intubation is increased in obese patients, monitoring and positioning obese patients under anaesthesia can also pose specific challenges [ 36 ]. Obesity is also associated with an increased risk of maternal mortality and anaesthesia-related maternal mortality [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is increased risk of incorrectly placing an epidural in obese patients as the distance to the epidural space is greater with increased BMI [ 36 , 37 ], risk of difficult intubation is increased in obese patients, monitoring and positioning obese patients under anaesthesia can also pose specific challenges [ 36 ]. Obesity is also associated with an increased risk of maternal mortality and anaesthesia-related maternal mortality [ 37 ]. From a midwife’s perspective, a 2011 study of midwives and other health professionals caring for obese childbearing women in NSW, Australia, found midwives were concerned about the rapid impact of the obesity epidemic on maternity services and that study participants felt increased pressure in the management of obese pregnant women and the complications associated with their BMI [ 38 ].…”
Section: Discussionmentioning
confidence: 99%